Respuesta :

1. y = √x-6 + 3 = 6 units to the right and 3 units up (d)

2. y = √x-3 - 6 = 3 units to the right and 6 units down (h)

3. y = √ x+3 - 6 = 3 units to the left and 6 units down (f)

4. y = √x-6 - 3 = 6 units to the right and 3 units down (e)

5. y = √x+6 + 3 = 6 units to the left and 3 units up (g)

6. y = √x + 6 - 3 = 6 units to the left and 3 units down (c)

7. y = √x-3 + 6 = 3 units to the right and 6 units up (b)

8. y = √x+ 3 + 6 = 3 units to the left and 6 units up (a)

Hope it is helpful ^_^

ACCESS MORE